Public Organizations In Uzbekistan – In The Interests Of The State And People - et. al., Khakimova Makhruya Abdulhaevna, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
On the basis of the work carried out in Uzbekistan, the role of public organizations is in full swing, which indicates that the role of the third sector is increasing. As the reforms carried out serve to increase the activity of citizens, the laws adopted in their place mean that they are in harmony with society, that is, the foundations of civil society are rising.